2008
DOI: 10.11606/issn.2316-9079.v7i1p45-90
|View full text |Cite
|
Sign up to set email alerts
|

Revisão taxonômica do complexo Bothrops neuwiedi (Serpentes, Viperidae) com descrição de uma nova espécie

Abstract: Taxonomic revision of the Bothrops neuwiedi complex (Serpentes, Viperidae) with description of a new species. Using a principal components analysis of morphological data of 1,759 specimens, we detected that the Bothrops neuwiedi complex (with 12 subspecies) is, actually, comprised of 7 full species, differing mainly by qualitative characteristics. One species was nominal. Five subspecies were elevated to the species level. Bothrops iglesiasi and the remaining B. neuwiedi subspecies entered in the synonymy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…In Bolivia, locals traditionally refer to the new species as "chuta", a local name for Bothrops mattogrossensis. It is important to note that, in the present study, we followed Silva & Rodrigues (2008) and referred to Bolivian populations of the "Bothrops neuwiedi" species group as B. mattogrossensis, but this classification should be taken with caution. A recent study (Carrasco et al 2019) found that those populations from Bolivia are morphologically similar and phylogenetically related to Bothrops diporus, hence a taxonomic re-arrangement may be required.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In Bolivia, locals traditionally refer to the new species as "chuta", a local name for Bothrops mattogrossensis. It is important to note that, in the present study, we followed Silva & Rodrigues (2008) and referred to Bolivian populations of the "Bothrops neuwiedi" species group as B. mattogrossensis, but this classification should be taken with caution. A recent study (Carrasco et al 2019) found that those populations from Bolivia are morphologically similar and phylogenetically related to Bothrops diporus, hence a taxonomic re-arrangement may be required.…”
Section: Discussionmentioning
confidence: 92%
“…In the past decades, several new pitviper species have been described from South America (Harvey 1994;Ferrarezzi & Freire 2001;Silva & Rodrigues 2008;Barbo et al 2012Barbo et al , 2016Carrasco et al 2019), and new discoveries seem likely to occur in the Andean Mountain Range (e.g., Esqueda et al 2005;Passos et al 2009;Rojas-Morales 2012). This vast territory harbors large regions of poorly explored terrain with diverse habitats, most of which have favorable conditions to house pitvipers, like the deep interandean valleys (Koch et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We assigned the distribution of the species to the following pre-defined Neotropical areas (according to Morrone, 2014): Antillean subregion: Antilles or West Indies (Greater and Lesser Antilles) and the Bahamas Islands, including the Bahamas, Cuban, Cayman Islands, Jamaica, Hispaniola, Puerto Rico and Lesser Antilles provinces; Brazilian subregion: Southern and central Mexico, Central America and north-western South America including the Mesoamerican, Pacific, Boreal Brazilian and Southwestern Amazonian dominions; Chacoan subregion: south-eastern South America including the Southeastern Amazonian, Chacoan and Parana dominions; and South American Transition Zone: highlands of the Andes between western Venezuela and northern Chile and central western Argentina, including the Paramo, Desert, Puna, Atacama, Prepuna and Monte provinces. The geographic distribution of each species of Bothrops was obtained from scientific literature (Campbell & Lamar, 1989Carrasco et al, 2012;Fenker, Tedeschi, Pyron, & Nogueira, 2014;Silva & Rodrigues, 2008;Uetz et al, 2018). Detailed information on the assignment of each species of Bothrops in the Neotropical areas adopted is provided in Appendix S2.…”
Section: Historical Biogeographic Analysismentioning
confidence: 99%
“…Comentarios: La presencia de esta especie en la Argentina es mencionada por primera vez por Ávila & Moreta (1995) sobre la base de dos ejemplares pertenecientes a la colección de la Fundación Miguel Lillo, identificados en ese momento como Bothrops neuwiedi bolivianus. Posteriormente, Silva & Rodrigues (2008) indican la presencia en el país basándose en el trabajo de Ávila & Moretta, pero sin haber examinado dicho material. La presencia real de esta especie en el elenco de las serpientes argentinas es puesta recientemente en duda por Carrasco et al (2019).…”
Section: Bothrops Matogrossensisunclassified